Method for producing modified dispersion and dispersion
Patent Information
- Application Number
- JP2021068662
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-14
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-04-14
AI Technical Summary
【0008】 本発明によれば、テトラフルオロエチレン系ポリマーの粒子と無機粒子と液状分散媒と非フッ素系レベリング剤とを含み、無機粒子の含有量が高い改質分散液が得られる。改質分散液は、分散安定性及び造膜性に優れており、均一性、加工性、他の材料との接着性及び低線膨張性に優れた厚い成形物を形成できる。
Abstract
Description
[Technical field]
[0001] The present invention relates to a modified dispersion containing particles of a tetrafluoroethylene-based polymer and a predetermined amount of inorganic particles, and a method for producing the dispersion. [Background technology]
[0002] Tetrafluoroethylene-based polymers such as polytetrafluoroethylene (PTFE) have excellent physical properties such as electrical characteristics, water and oil repellency, chemical resistance, and heat resistance, and are used in various industrial applications such as printed circuit boards. Dispersions containing particles of tetrafluoroethylene-based polymers are known as coating agents used to impart the above physical properties to the surface of a substrate. Such dispersions have attracted attention as materials with excellent electrical properties such as low dielectric constant and low dielectric loss tangent, which are useful for forming dielectric layers of printed circuit boards compatible with high frequency bands.
[0003] In order to improve the storage stability and dispersion stability of such a dispersion, Patent Document 1 proposes blending a fluorosurfactant and ceramics into the dispersion. Patent Documents 2 and 3 each propose blending a fluorosurfactant and a specific polyvinyl alcohol into the dispersion. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-194017 A [Patent Document 2] JP 2020-186351 A [Patent Document 3] JP 2017-210549 A Summary of the Invention [Problem to be solved by the invention]
[0005] Although tetrafluoroethylene-based polymers have excellent electrical properties, dispersions containing the particles thereof have poor dispersion stability, miscibility with other materials, and adhesion when molded products are formed. When a fluorosurfactant is added as a dispersion component, the dispersion stability of the dispersion is improved, but the film-forming properties of the dispersion are likely to be reduced. Specifically, it becomes difficult to form a thick molded product, and the uniformity, processability, and adhesion of the molded product are likely to be reduced. The present inventors have found that this tendency is significant when a large amount of inorganic particles are added to the dispersion as a dispersion component that improves the physical properties of the molded product.
[0006] The present inventors have found, through intensive research, that if a non-fluorine-based leveling agent is added to the dispersion liquid containing tetrafluoroethylene-based polymer particles and inorganic particles to reduce the surface tension and modify the dispersion liquid, the dispersion liquid containing a large amount of inorganic particles can have excellent dispersion stability and film-forming properties.Furthermore, they have found that the thick molded product having excellent uniformity, processability, adhesion to other materials and low linear expansion can be formed from the modified dispersion liquid. An object of the present invention is to provide a method for producing a modified dispersion which contains tetrafluoroethylene polymer particles, inorganic particles, a liquid compound, and a non-fluorinated leveling agent and which can form a thick molded product having excellent uniformity, processability, adhesion to other materials, and low linear expansion, and to provide such a dispersion. [Means for solving the problem]
[0007] The present invention has the following aspects. <1> A method for producing a modified dispersion liquid, comprising adding a non-fluorine-based leveling agent to a dispersion liquid containing tetrafluoroethylene-based polymer particles, inorganic particles, and a liquid dispersion medium, the proportion of the inorganic particles in the total amount being 20 to 60 mass %, thereby reducing the surface tension of the dispersion liquid to obtain a modified dispersion liquid. <2> The particles of the tetrafluoroethylene-based polymer include particles of a heat-fusible tetrafluoroethylene-based polymer and particles of a non-heat-fusible tetrafluoroethylene-based polymer. <1> Manufacturing method. <3> The melting temperature of the tetrafluoroethylene polymer is 200 to 325°C. <1> or <2> Manufacturing method. <4> The tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer having a carbonyl group-containing group or a hydroxyl group-containing group. <1> ~ <3> A manufacturing method of any one of the above. <5> The inorganic particles are silica particles. <1> ~ <4> A manufacturing method of any one of the above. <6> The non-fluorine-based leveling agent is at least one selected from the group consisting of (meth)acrylic leveling agents, silicone leveling agents, and alcohol alkoxylates. <1> ~ <5> A manufacturing method of any one of the above. <7> The liquid dispersion medium is at least one selected from the group consisting of water, amides, ketones, and esters. <1> ~ <6> A manufacturing method of any one of the above. <8> The difference between the surface tension of the modified dispersion and the surface tension of the dispersion is 1 mN / m or less. <1> ~ <7> A manufacturing method of any one of the above. <9> the dispersion further comprises an aromatic polymer; <1> ~ <8> A manufacturing method of any one of the above. <10> The dispersion further contains a nonionic surfactant. <1> ~ <9> A manufacturing method of any one of the above. <11> <1> ~ <10> a modified dispersion obtained by any one of the above-mentioned manufacturing methods is applied to a surface of a substrate, and heated to form a polymer layer containing the tetrafluoroethylene-based polymer and the inorganic particles, thereby obtaining a laminate having a substrate layer constituted by the substrate and the polymer layer. <12> The thickness of the polymer layer is 25 μm or more. <11> Manufacturing method. <13> The ten-point average roughness of the surface of the substrate is 0.1 μm or less; <11> or <12> Manufacturing method. <14> A modified dispersion liquid comprising tetrafluoroethylene-based polymer particles, inorganic particles, a liquid dispersion medium, and at least one non-fluorine-based leveling agent selected from the group consisting of a (meth)acrylic leveling agent, a silicone leveling agent, and an alcohol alkoxylate, wherein the proportion of the tetrafluoroethylene-based polymer particles and the proportion of the inorganic particles in the total amount are 5 to 40 mass% and 20 to 60 mass%, respectively. <15> The liquid dispersion medium is at least one selected from the group consisting of water, amides, ketones, and esters. <14> Modified dispersion of. Effect of the Invention
[0008] According to the present invention, a modified dispersion liquid containing tetrafluoroethylene-based polymer particles, inorganic particles, a liquid dispersion medium, and a non-fluorinated leveling agent and having a high content of inorganic particles can be obtained. The modified dispersion liquid has excellent dispersion stability and film-forming properties, and can form a thick molded product having excellent uniformity, processability, adhesion to other materials, and low linear expansion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The following terms have the following meanings. A "tetrafluoroethylene-based polymer" is a polymer containing units based on tetrafluoroethylene, and hereinafter may also be simply referred to as an "F polymer." "Average particle size (D50)" is the cumulative 50% volumetric diameter of a target object (particle) determined by laser diffraction / scattering. In other words, particle size distribution is measured by laser diffraction / scattering, and a cumulative curve is calculated with the total volume of the target object group as 100%, and the particle size is the point on the cumulative curve where the cumulative volume is 50%. The D50 of a target object is determined by dispersing the target object in water and analyzing it by the laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). "Average particle size (D90)" is the cumulative volume particle size of a subject, and is the volume-based cumulative 90% diameter of a subject, which is calculated in the same manner as "D50". The "melting temperature of a polymer" is the temperature corresponding to the maximum value of the melting peak of the polymer as measured by differential scanning calorimetry (DSC). "Thermal melt resin (polymer)" means a resin (polymer) having melt fluidity, which has a melt flow rate of 1 to 1000 g / 10 min at a temperature 20°C or more higher than the melting temperature of the resin (polymer) under a load of 49 N. The term "non-thermofusible resin (polymer)" refers to a non-melt-flowable resin (polymer) at which there is no temperature at which the melt flow rate is 1 to 1000 g / 10 min under a load of 49 N. The "glass transition point (Tg) of a polymer" is a value measured by analyzing a polymer using a dynamic mechanical analysis (DMA) method. "Viscosity" refers to the viscosity of a dispersion or liquid composition measured using a Brookfield viscometer at 25° C. and a rotation speed of 30 rpm. The measurement is repeated three times, and the average value of the three measured values is used. The "thixotropy ratio" is a value calculated by dividing the viscosity η1 of a dispersion or liquid composition measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement is repeated three times, and the average value of the three measured values is used. The term "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit."
[0010] The manufacturing method of the present invention (hereinafter also referred to as "this method") is a method in which a non-fluorine-based leveling agent is added to a dispersion (hereinafter also referred to as "original dispersion") containing tetrafluoroethylene polymer (F polymer) particles (hereinafter also referred to as "F particles"), inorganic particles, and a liquid dispersion medium, with the proportion of inorganic particles in the total amount being 20 to 60 mass%, to obtain a modified dispersion by lowering the surface tension of the original dispersion. The modified dispersion in this method is a dispersion containing F particles, inorganic particles, a liquid compound, and a non-fluorine-based leveling agent. The modified dispersion obtained by this method has excellent dispersion stability and film-forming properties, and can form thick molded products with excellent uniformity, processability, adhesion to other materials, and low linear expansion. The reason for this is not entirely clear, but is thought to be as follows.
[0011] When the surface tension of the dispersion is high, the F polymer, which has a low surface tension, is less likely to interact with the inorganic particles and the liquid dispersion medium, and the F particles tend to aggregate. On the other hand, when the surface tension of the dispersion is low, the dispersion tends to spread thinly when applied to a substrate to form a molded product, making it difficult to obtain a thick, uniform molded product. These tendencies tend to become more pronounced as the proportion of inorganic particles in the dispersion increases. In this method, a non-fluorine-based leveling agent is added to an original dispersion liquid containing F particles, inorganic particles, and a liquid dispersion medium, which can appropriately reduce the surface tension of the modified dispersion liquid while suppressing the aggregation of the F particles.
[0012] Furthermore, the addition of the leveling agent improves the rheology (viscosity, thixotropy ratio, etc.) of the modified dispersion, and the settling of the F particles and inorganic particles is easily suppressed. Furthermore, the non-fluorine-based leveling agent also acts as a binder, and the physical properties of the molded product formed from the modified dispersion are easily improved. Specifically, the non-fluorine-based leveling agent promotes adhesion between the F polymer and the inorganic particles in the molded product, and the low linear expansion property of the molded product is easily improved. In addition, the non-fluorine-based leveling agent is unevenly distributed on the surface of the molded product, improving the adhesion of the surface of the molded product, and making it easier to suppress the powdering of the F particles and inorganic particles. As a result, it is believed that this method can produce a modified dispersion liquid with excellent handling properties such as dispersion stability and film-forming properties, and can then be used to form thick molded products with excellent uniformity, processability, adhesion to other materials, and low linear expansion properties.
[0013] The F polymer in the present invention is a polymer containing units based on tetrafluoroethylene (hereinafter also referred to as "TFE") (hereinafter also referred to as "TFE units"). The F polymer may be either heat-fusible or non-heat-fusible. When the F polymer is heat-meltable, the melting temperature is preferably 200° C. or higher, more preferably 240° C. or higher, and even more preferably 260° C. or higher. The melting temperature of the F polymer is preferably 325° C. or lower, more preferably 320° C. or lower. The melting temperature of the F polymer is particularly preferably 200 to 320° C.
[0014] The glass transition point of the F polymer is preferably 50° C. or higher, more preferably 75° C. or higher. The glass transition point of the F polymer is preferably 150° C. or lower, more preferably 125° C. or lower. The surface tension of the F polymer is preferably 16 to 26 mN / m, more preferably 16 to 20 mN / m. The surface tension of the F polymer can be measured by placing a droplet of a wettability index reagent (manufactured by Wako Pure Chemical Industries, Ltd.) on a flat plate made of the F polymer. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass. An F polymer with a high fluorine content has excellent physical properties such as electrical properties, but has a low surface tension and is prone to a decrease in dispersion stability in the original dispersion. In the modified dispersion, however, the dispersion stability of such an F polymer is likely to be improved due to the above-mentioned mechanism of action.
[0015] F polymer includes polytetrafluoroethylene (PTFE), the polymer that comprises TFE unit and the unit based on ethylene, the polymer that comprises TFE unit and the unit based on propylene, the polymer that comprises TFE unit and the unit based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE unit) (PFA), the polymer that comprises TFE unit and the unit based on hexafluoropropylene (FEP), the polymer that comprises TFE unit and the unit based on fluoroalkylethylene, the polymer that comprises TFE unit and the unit based on chlorotrifluoroethylene, and PFA or FEP is preferred, and PFA is more preferred.The above-mentioned polymer may further comprise the unit based on other comonomers. As PAVE, CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE") is preferred, and PPVE is more preferred.
[0016] The PTFE may be a non-thermofusible PTFE or a thermofusible PTFE. The F polymer preferably has an oxygen-containing polar group, which facilitates the formation of microspherulites at the molecular aggregate level, improves the wettability of the F particles, and facilitates the development of the above-mentioned effects of the present invention. The oxygen-containing polar group may be contained in a unit in the F polymer, or may be contained in a terminal group of the main chain of the F polymer. Examples of the latter embodiment include an F polymer having an oxygen-containing polar group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer having an oxygen-containing polar group obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment. The oxygen-containing polar group is preferably a hydroxyl group-containing group, a carbonyl group-containing group, or a phosphono group-containing group, and from the viewpoint of dispersion stability of the modified dispersion, a hydroxyl group-containing group and a carbonyl group-containing group are more preferable, and a carbonyl group-containing group is even more preferable.
[0017] The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is a group containing a carbonyl group (>C(O)), and is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) or a carbonate group (-OC(O)O-), and more preferably an acid anhydride residue. In this case, the F particles are likely to interact with the inorganic particles and the liquid dispersion medium, and the modified dispersion is likely to have excellent liquid physical properties such as dispersion stability.
[0018] The F polymer is preferably a polymer having a carbonyl group-containing group including TFE units and PAVE units, more preferably a polymer containing units based on a monomer having a TFE unit, a PAVE unit and a carbonyl group-containing group, and even more preferably a polymer containing these units in the order of 90 to 99 mol%, 0.5 to 9.97 mol%, and 0.01 to 3 mol% relative to the total units. The presence of a carbonyl group-containing group is preferable from the viewpoint of further improving the affinity of the F polymer with inorganic particles and liquid dispersion media, and the adhesion with other materials.
[0019] When the F polymer has a carbonyl group-containing group, the number of carbonyl group-containing groups in the F polymer is 1×10 6 The number of carbonyl-containing groups per unit is preferably 10 to 5000, more preferably 100 to 3000, and further preferably 800 to 1500. The number of carbonyl-containing groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133. In addition, the monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"). Specific examples of such polymers include the polymers described in WO 2018 / 16644.
[0020] The D50 of the F particles in the present invention is preferably 0.1 to 25 μm. The D50 of the F particles is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 8 μm or less. The D50 of the F particles is preferably 0.2 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. With a D50 in this range, the fluidity and dispersion stability of the F particles tend to be good. From the viewpoint of dispersion stability, the specific surface area of F particles is 1 to 25 m 2 / g is preferable, and 1 to 8m 2 / g is more preferred.
[0021] The F particles may be one type or two or more types. When two types of F particles are used, the F particles preferably include particles of a heat-fusible F polymer and particles of a non-heat-fusible F polymer, and more preferably include particles of an F polymer (preferably a polymer having an oxygen-containing polar group containing the above-mentioned TFE unit and PAVE unit) having a melting temperature of 200 to 320°C and particles of a non-heat-fusible PTFE. In this case, it is believed that when the liquid properties are modified by adding a non-fluorinated leveling agent to the original dispersion, the non-thermofusible F polymer undergoes moderate fibrillation while maintaining its physical properties. As a result, inorganic particles are more easily supported in the molded product formed from the modified dispersion, and the strength of the molded product is more likely to be improved.
[0022] In this case, the proportion of the former particles in the total of the former particles and the latter particles is preferably 50% by mass or less, more preferably 25% by mass or less, and in this case, the proportion is preferably 0.1% by mass or more, more preferably 1% by mass or more. In this case, preferred embodiments are those in which the particles of the F polymer having a melting temperature of 200 to 320°C have a D50 of 0.1 to 1 μm and the particles of the non-thermofusible PTFE have a D50 of 0.1 to 1 μm, and those in which the particles of the F polymer having a melting temperature of 200 to 320°C have a D50 of 1 to 4 μm and the particles of the non-thermofusible PTFE have a D50 of 0.1 to 1 μm.
[0023] The F particles may contain resins other than the F polymer or inorganic particles, but preferably contain the F polymer as the main component. The content of the F polymer in the F powder is preferably 80% by mass or more, more preferably 100% by mass. Examples of resins other than F polymer include heat-resistant resins such as aromatic polyester, polyamideimide, (thermoplastic) polyimide, polyphenylene ether, polyphenylene oxide, and maleimide. Examples of inorganic substances contained in the inorganic particles include silicon oxide (silica), metal oxides (beryllium oxide, cerium oxide, alumina, soda alumina, magnesium oxide, zinc oxide, titanium oxide, and the like), boron nitride, and magnesium metasilicate (steatite). At least a portion of the surface of the inorganic particles may be surface-treated.
[0024] F particles containing a resin or inorganic particles other than an F polymer may have a core-shell structure having an F polymer as the core and a resin or inorganic particles other than an F polymer as the shell, or may have a core-shell structure having an F polymer as the shell and a resin or inorganic particles other than an F polymer as the core. Such F particles are obtained, for example, by bonding (collision, aggregation, etc.) particles of an F polymer and particles of a resin or inorganic particles other than an F polymer. The content of F particles in the modified dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, based on the total amount of the modified dispersion. The content of F particles is preferably 40% by mass or less, more preferably 30% by mass or less, based on the total amount of the modified dispersion.
[0025] The inorganic particles in the present invention may contain components other than the inorganic compound, but preferably contain the inorganic compound as the main component. The content of the inorganic compound in the inorganic particles is preferably 80 mass % or more, more preferably 100 mass %. The inorganic particles may be used alone or in combination of two or more kinds. The shape of the inorganic particles may be any of spherical, acicular (fibrous), and plate-like, preferably plate-like or spherical, more preferably spherical, and even more preferably substantially spherical. Note that substantially spherical inorganic particles refer to inorganic particles in which the ratio of spherical particles having a ratio of minor axis to major axis of 0.7 or more accounts for 95% or more when observed with a scanning electron microscope (SEM). In this case, the inorganic particles and the F particles are likely to interact with each other, and the modified dispersion is likely to have excellent physical properties such as dispersion stability. In addition, the molded product formed from the modified dispersion is likely to have excellent electrical properties and low linear expansion.
[0026] Specific shapes of the inorganic particles include spherical, scale-like, layered, leaf-like, apricot kernel-like, columnar, cockscomb-like, equiaxial, leaf-like, micaceous, block-like, tabular, wedge-like, rosette-like, net-like, and prismatic shapes. The inorganic particles are preferably carbon particles, nitride particles and inorganic oxide particles, more preferably carbon fiber particles, boron nitride particles, aluminum nitride particles, beryllia particles, silicate particles (silica particles, wollastonite particles, talc particles) and metal oxide particles (cerium oxide, aluminum oxide, magnesium oxide, zinc oxide, titanium oxide, etc.), and from the viewpoint of improving the dispersion stability of the modified dispersion and the electrical properties and low linear expansion properties of the molded product formed from the modified dispersion, boron nitride particles and silica particles are further preferable, and silica particles are particularly preferable.
[0027] The D50 of the inorganic particles is preferably 20 μm or less, more preferably 10 μm or less. The D50 is preferably 0.01 μm or more, more preferably 0.1 μm or more. The ratio of the D50 of the inorganic particles to the D50 of the F particles is preferably 0.01 or more, more preferably 0.1 or more. The ratio is preferably 20 or less, more preferably 10 or less. The specific surface area of inorganic particles is 1 to 20 m 2 / g is preferred. In order to improve the wettability of the inorganic particles, at least a portion of the surface of the inorganic particles may be surface-treated with a silane coupling agent (3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-isocyanatopropyltriethoxysilane, etc.).
[0028] Specific examples of suitable inorganic particles include silica particles (such as the "Admafine (registered trademark)" series manufactured by Admatechs Co., Ltd.), zinc oxide surface-treated with an ester such as propylene glycol dicaprate (such as the "FINEX (registered trademark)" series manufactured by Sakai Chemical Industry Co., Ltd.), spherical fused silica (such as the "SFP (registered trademark)" series manufactured by Denka Co., Ltd.), titanium oxide coated with polyhydric alcohol and inorganic substances (such as the "Tipaque (registered trademark)" series manufactured by Ishihara Sangyo Kaisha, Ltd.), and rutile-type titanium oxide surface-treated with alkylsilane (such as the "Taika Co., Ltd. "JMT (registered trademark)" series, etc.), hollow silica particles ("E-SPHERES" series manufactured by Taiheiyo Cement Corporation, "Silinax" series manufactured by Nippon Steel Mining Co., Ltd., "Ecocospher" series manufactured by Emerson & Cumming Co., Ltd., etc.), talc particles ("SG" series manufactured by Nippon Talc Co., Ltd., etc.), steatite particles ("BST" series manufactured by Nippon Talc Co., Ltd., etc.), boron nitride particles ("UHP" series manufactured by Showa Denko KK, "Denka Boron Nitride" series ("GP", "HGP" grades), etc.) manufactured by Denka Co., Ltd.
[0029] The proportion of the inorganic particles in the total amount of the modified dispersion is 20 to 60% by mass. The proportion of the inorganic particles is preferably 30% by mass or more. The proportion of the inorganic particles is preferably 50% by mass or less. In the modified dispersion, the ratio of the content of the inorganic particles to the content of the F particles is preferably 0.8 or more, more preferably more than 1. The ratio is preferably 3 or less, more preferably 2 or less. In this case, the modified dispersion is likely to have excellent dispersion stability and film-forming properties, and a molded product having excellent uniformity, adhesion, low linear expansion, and electrical properties is likely to be formed.
[0030] The liquid dispersion medium in the present invention means a compound that is liquid at atmospheric pressure and 25° C. The liquid dispersion medium is preferably at least one selected from the group consisting of hydrocarbons, water, alcohols, amides, ketones, and esters, and more preferably at least one selected from the group consisting of water, amides, ketones, and esters. The boiling point of the liquid dispersion medium is preferably 50 to 240° C. One type of liquid dispersion medium may be used alone, or two or more types may be used in combination. Alcohols include methanol, ethanol, isopropanol, and glycol.
[0031] Examples of the amide include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone. Examples of the ketone include acetone, methyl ethyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl n-pentyl ketone, methyl isopentyl ketone, 2-heptanone, cyclopentanone, cyclohexanone, and cycloheptanone.
[0032] Examples of the ester include methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethyl 3-ethoxypropionate, γ-butyrolactone, and γ-valerolactone. Specific examples of suitable liquid dispersion media include water, N-methyl-2-pyrrolidone, γ-butyrolactone, cyclohexanone and cyclopentanone, with water being preferred from the viewpoints of dispersion stability, film-forming properties and handling properties of the modified dispersion. The content of the liquid dispersion medium in the modified dispersion is preferably 20 to 70% by mass, more preferably 30 to 50% by mass, in which case the liquid physical properties such as the dispersion stability of the modified dispersion are more likely to be improved.
[0033] The non-fluorine-based leveling agent in the present invention is a leveling agent that does not have a fluorine atom, and is preferably a (meth)acrylic leveling agent, a silicone leveling agent or an alcohol alkoxylate, and from the viewpoint of improving the dispersion stability and film-forming properties of the modified dispersion, a (meth)acrylic leveling agent is more preferable. The (meth)acrylic leveling agent means a leveling agent having a structure derived from (meth)acrylic acid or (meth)acrylate. The (meth)acrylic leveling agent may be a polymer of (meth)acrylic acid or (meth)acrylate, or a non-polymeric compound having a (meth)acryloyloxy group, which is a residue thereof.
[0034] The silicone-based leveling agent means a leveling agent having a siloxane structure. The silicone-based leveling agent may be a polymer having a polysiloxane structure, or a compound having a siloxane structure such as a hydrolyzable silyl group. Incidentally, (meth)acrylic acid is a general term for methacrylic acid and acrylic acid, (meth)acrylate is a general term for methacrylate and acrylate, and (meth)acryloyloxy group is a general term for methacryloyloxy group and acryloyloxy group.
[0035] The (meth)acrylic leveling agent is preferably a polymer of at least one (meth)acrylate selected from the group consisting of (meth)acrylic acid, polyether-modified (meth)acrylate, silicone-modified (meth)acrylate, and polyether-silicone-modified (meth)acrylate, or a non-polymeric compound having a residue of one of the above (meth)acrylates. In addition, polyether-silicone modified (meth)acrylate refers to (meth)acrylate modified with both polyether and silicone.
[0036] The silicone leveling agent is preferably polyether-modified polydimethylsiloxane, polyether-modified siloxane, polyetherester-modified hydroxyl group-containing polydimethylsiloxane, polyether-modified acrylic group-containing polydimethylsiloxane, polyester-modified acrylic group-containing polydimethylsiloxane, polymethylalkylsiloxane or epoxy-modified polydimethylsiloxane. The non-fluorine-based leveling agent may be used alone or in combination of two or more kinds. The average molecular weight of the non-fluorinated leveling agent is preferably from 100 to 200000. In this case, the modified dispersion tends to have excellent dispersion stability and film-forming properties.
[0037] Specific examples of non-fluorinated leveling agents include "BYK-325", "BYK-345", "BYK-346", "BYK-347", "BYK-349", "BYK-UV3500", "BYK-380 N", "BYK-381", "BYK-399", "BYK-3440", "BYK-3550", "BYK-3560", "BYK-3565", "BYK-3566", "BYK-SILCLEAN 3700", "BYK-SILCLEAN 3701", "BYK-SILCLEAN 3720", "BYK-DYNWET 800 N", "BYKETOL-AQ", and "BYKETOL-WS" (all manufactured by BYK-Chemie Japan Co., Ltd.), "Polyflow WS", "Polyflow WS-30", and "Polyflow WS-314" (all manufactured by Kyoeisha Chemical Co., Ltd.). The proportion of the non-fluorinated leveling agent in the total amount of the modified dispersion is preferably 0.1 to 15 mass %, more preferably 1 to 5 mass %, in which case the liquid properties such as the dispersion stability of the modified dispersion are more likely to be improved.
[0038] The raw dispersion in this method can be produced by mixing F particles, inorganic particles, and a liquid dispersion medium. Examples of the mixing method include a method in which the F particles and inorganic particles are added to a liquid dispersion medium all at once and mixed; a method in which the F particles and inorganic particles are added sequentially to a liquid dispersion medium and mixed; a method in which the F particles and inorganic particles are mixed to form a powder mixture and then mixed with a liquid dispersion medium; a method in which the F particles and liquid dispersion medium, and the inorganic particles and liquid dispersion medium are mixed in advance, respectively, and the two resulting mixtures are further mixed; and the method in which the F particles and inorganic particles are mixed to form a powder mixture and then mixed with a liquid dispersion medium is preferred.
[0039] The mixing method for preparing the raw dispersion may be either a batch method or a continuous method. Examples of equipment used for mixing include stirring devices equipped with uniaxial or multiaxial blades (stirring impellers) such as propeller blades, turbine blades, paddle blades, and shell-shaped blades, as well as stirring using a Henschel mixer, pressure kneader, Banbury mixer, or planetary mixer; mixing using a disperser that uses media such as a ball mill, attritor, basket mill, sand mill, sand grinder, Dyno Mill (a bead mill using grinding media such as glass beads or zirconium oxide beads), Dispermat, SC mill, spike mill, or agitator mill; and mixing using a disperser that does not use media, such as high-pressure homogenizers such as a Microfluidizer, Nanomizer, or Ultimizer, ultrasonic homogenizer, Dissolver, Disper, or high-speed impeller disperser.
[0040] Among them, the device used for mixing is preferably a Henschel mixer, a pressure kneader, a Banbury mixer or a planetary mixer, and more preferably a planetary mixer. A planetary mixer has two agitating blades that rotate and revolve around each other, and is designed to agitate and mix the mixture in the mixing vessel. Therefore, there is little dead space in the mixing vessel where the agitating blades do not reach, reducing the load on the blades and allowing the contents to be mixed to a high degree. When the raw dispersion further contains optional additive components such as an aromatic polymer and a nonionic surfactant, which will be described later, these can be mixed at any stage. The mixing method and mixing device may be the same as those described above.
[0041] In this method, a non-fluorinated leveling agent is added to the original dispersion to reduce its surface tension, thereby obtaining a modified dispersion. The non-fluorinated leveling agent may be added directly to the original dispersion, or may be added to the original dispersion as a mixture with a liquid dispersion medium. The liquid dispersion medium may be the same as or different from the liquid dispersion medium contained in the original dispersion. As the method and device for mixing the raw dispersion and the non-fluorinated leveling agent, the above-mentioned mixing method and device for preparing the raw dispersion can be mentioned.
[0042] The surface tension of the modified dispersion in the present invention is lower than that of the original dispersion. The difference between the surface tension of the modified dispersion and the surface tension of the original dispersion is preferably 0.1 mN / m or more, more preferably 0.2 mN / m or more. The difference is preferably 1 mN / m or less, more preferably 0.5 mN / m or less. In this case, the surface tension of the original dispersion is appropriately reduced, the aggregation of the F particles is easily eliminated, and the modified dispersion is likely to have excellent dispersion stability and film-forming properties.
[0043] Preferably, the modified dispersion further comprises an aromatic polymer. The aromatic polymer may be thermoplastic or thermosetting. The aromatic polymer may be dissolved in the modified dispersion or may be dispersed without being dissolved. The aromatic polymer may be included in the modified dispersion as a precursor thereof. The aromatic polymer is preferably an aromatic imide-based polymer, more preferably an aromatic polyimide, an aromatic polyimide precursor (polyamic acid or a salt thereof), an aromatic polyamideimide, an aromatic polyamideimide precursor, an aromatic polyetherimide or an aromatic polyetherimide precursor, and more preferably an aromatic polyimide precursor or an aromatic polyamideimide. These aromatic polymers may be modified aromatic polymers further having an acidic group such as a carboxylic acid group or a phenolic hydroxyl group introduced therein. When the modified dispersion contains water as the liquid dispersion medium, the aromatic polymer is preferably water-soluble, more preferably a precursor of a water-soluble aromatic polyamideimide or a precursor of a water-soluble aromatic polyimide.
[0044] The water-soluble aromatic polymer can be prepared by adjusting the acid value or the basicity of the modified dispersion. For example, when the aromatic polymer is an aromatic polyamic acid, it can be prepared by reacting the aromatic polyamic acid with aqueous ammonia or an organic amine to obtain a polyamic acid salt. Specifically, the aromatic polymer in this case has an acid value of preferably 20 to 100 mg KOH / g, more preferably 35 to 70 mg KOH / g, and the modified dispersion has a pH of preferably 5 to 10, more preferably 7 to 9. If the acid value of the aromatic polymer and the pH of the modified dispersion are within the above ranges, not only is the dispersion stability of the modified dispersion improved, but when a molded product is formed from the modified dispersion, the aromatic polymer is highly dispersed, making it easier to improve the physical properties (ultraviolet light absorbency, flexibility, adhesion, etc.) of the molded product. Specific examples of aromatic polymers include "Ultem 1000F3SP" (manufactured by SABIC), "HPC-1000" and "HPC-2100D" (all manufactured by Showa Denko Materials KK).
[0045] The original dispersion in the present invention preferably further contains a nonionic surfactant. The hydrophilic site of the nonionic surfactant preferably has an oxyalkylene group or an alcoholic hydroxyl group. The oxyalkylene group may be composed of one type or two or more types. In the latter case, the different types of oxyalkylene groups may be arranged randomly or in a block form. The oxyalkylene group is preferably an oxyethylene group. The hydrophobic portion of the nonionic surfactant preferably has an acetylene group, a polysiloxane group, a perfluoroalkyl group, or a perfluoroalkenyl group. In other words, the surfactant is preferably a polyoxyalkylene alkyl ether, an acetylene-based surfactant, a silicone-based surfactant, or a fluorine-based surfactant, and more preferably a silicone-based surfactant. As the silicone surfactant, an organopolysiloxane having a polyoxyalkylene structure as a hydrophilic group and a polydimethylsiloxane structure as a hydrophobic group is preferred. When the silicone surfactant is contained, a polyoxyalkylene alkyl ether and a silicone surfactant may be used in combination from the viewpoint of improving the long-term storage stability of the modified dispersion.
[0046] Specific examples of nonionic surfactants include the "Ftergent" series (manufactured by Neos Co., Ltd., Ftergent is a registered trademark), the "Surflon" series (manufactured by AGC Seimi Chemical Co., Ltd., Surflon is a registered trademark), the "Megafac" series (manufactured by DIC Corporation, Megafac is a registered trademark), the "Unidyne" series (manufactured by Daikin Industries, Ltd., Unidyne is a registered trademark), "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (manufactured by BYK Japan Co., Ltd.), "KF-6011", "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.), the "Tergitol" series (manufactured by The Dow Chemical Company, "Tergitol TMN-100X", etc.), "Lutensol T08", "Lutensol XL70", "Lutensol XL80", "Lutensol XL90", "Lutensol Examples of such compounds include "XP80", "Lutensol M5" (both manufactured by BASF), "Newcol 1308FA", "Newcol 1310" (both manufactured by Nippon Nyukazai Co., Ltd.), "Leocol TDN-90-80", and "Leocol SC-90" (both manufactured by Lion Specialty Chemicals). When the modified dispersion liquid contains a nonionic surfactant, the content of the nonionic surfactant in the modified dispersion liquid is preferably from 0.1 to 15 mass %, more preferably from 1 to 10 mass %.
[0047] When the modified dispersion contains water as a liquid dispersion medium, the pH of the modified dispersion is preferably from 5 to 10, more preferably from 7 to 9, from the viewpoint of long-term storage stability. The modified dispersion may further comprise a pH adjuster or pH buffer. pH adjusters include amines, ammonia, and citric acid. Examples of pH buffers include tris(hydroxymethyl)aminomethane, ethylenediaminetetraacetic acid, ammonium hydrogen carbonate, ammonium carbonate, and ammonium acetate. The pH adjuster or buffer may be added either before or during mixing.
[0048] The modified dispersion may be subjected to a defoaming treatment, which is preferably carried out using a planetary centrifugal mixer. In addition to the above-mentioned components, the modified dispersion may further contain additives such as a thixotropic agent, a viscosity regulator, an antifoaming agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, a flame retardant, an antiseptic, an antifungal agent, and an organic filler.
[0049] The viscosity of the modified dispersion is preferably 10 mPa·s or more, more preferably 50 mPa·s or more, and even more preferably 100 mPa·s or more. The viscosity of the modified dispersion is preferably 10,000 mPa·s or less, more preferably 3,000 mPa·s or less, and even more preferably 1,000 mPa·s or less. In this case, the modified dispersion tends to have excellent dispersion stability, film-forming properties, etc. The thixotropy ratio of the modified dispersion is preferably 1.0 or more. The thixotropy ratio of the modified dispersion is preferably 3.0 or less, more preferably 2.0 or less. In this case, the modified dispersion has excellent liquid physical properties such as dispersion stability, and is likely to form a denser molded product.
[0050] The dispersion layer ratio of the modified dispersion is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. The modified dispersion has excellent dispersion stability, so that the dispersion layer ratio is likely to be in the above range. Here, the dispersion layer ratio is a value calculated by the following formula from the height of the entire dispersion in the screw tube and the height of the sedimentation layer (dispersion layer) before and after standing when the dispersion (18 mL) is placed in a screw tube (internal volume: 30 mL) and left to stand for 14 days at 25° C. If no sedimentation layer is observed after standing and there is no change in the state, it is considered that there is no change in the height of the entire dispersion, and the dispersion layer ratio is 100%. Dispersion layer rate (%) = (height of sedimentation layer) / (total height of dispersion liquid) x 100
[0051] The solid content of the modified dispersion is preferably 30% by mass or more, more preferably 40% by mass or more, and from the viewpoint of dispersion stability, is preferably 80% by mass or less, more preferably 60% by mass or less. The solid content of the modified dispersion means the total amount of the substances that form the solid content in the molded product formed from the modified dispersion. For example, when the dispersion contains F particles, inorganic particles, and aromatic polyimide, the total content of these components is the solid content of the modified dispersion.
[0052] In the modified dispersion, the proportion of the F particles in the solid content is preferably 10% by mass or more, more preferably 20% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less. In the modified dispersion, the proportion of inorganic particles in the solid content is preferably 20% by mass or more, more preferably 40% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less.
[0053] The modified dispersion can be used in applications such as forming an insulating layer for printed wiring boards, bonding ceramic parts or metal parts together in vehicle engines, imparting corrosion resistance to heat exchangers and the fins or tubes that constitute them, impregnating and drying coils used in thermal interface materials, power module substrates, and power devices such as motors to form a thermally conductive, heat-resistant coating layer, and coating the inside and outside of glass containers such as medical vials and syringes.
[0054] The modified dispersion has excellent liquid physical properties such as dispersion stability, and due to the above-mentioned mechanism of action, it is possible to form a molded product based on the F polymer and inorganic particles, which has excellent physical properties. In addition, it is possible to form a molded product that exhibits strong adhesion to a substrate. The modified dispersion is applied to the surface of a substrate and heated to form a layer containing an F polymer and inorganic particles (hereinafter also referred to as the "F layer"). This produces a laminate (hereinafter also referred to as the "laminate") having a substrate layer composed of the substrate and an F layer as a molded product. Suitable embodiments of the laminate include a metal-clad laminate having a metal foil and an F layer formed on at least one surface thereof, and a multilayer film having a resin film and an F layer formed on at least one surface thereof.
[0055] The ten-point average roughness of the surface of the substrate is preferably 0.1 μm or less, more preferably 0.05 μm or less. The ten-point average roughness of the surface of the substrate is preferably 0.01 μm or more. Since an F layer having excellent adhesiveness can be formed from the modified dispersion, the laminate is likely to have excellent peel strength even when a substrate having excellent smoothness is used. In producing the above laminate, it is sufficient that an F layer is formed on at least one surface of the substrate. An F layer may be formed on only one surface of the substrate, or an F layer may be formed on both surfaces of the substrate. The surface of the substrate may be treated with a silane coupling agent or the like.
[0056] The modified dispersion can be applied by any of a variety of methods, including spraying, roll coating, spin coating, gravure coating, microgravure coating, gravure offset, knife coating, kiss coating, bar coating, die coating, fountain-meyer bar, and slot die coating. The F layer is preferably formed by removing the liquid dispersion medium by heating, and then baking the F polymer by further heating. It is preferable to blow air in the step of removing the liquid dispersion medium. After removing the liquid dispersion medium, the substrate is preferably heated to a temperature range in which the F polymer is baked, and the F polymer is preferably baked, for example, in the range of 300 to 400° C. The F layer preferably contains a baked product of F particles.
[0057] The F layer is formed through the steps of coating the modified dispersion, drying, and firing as described above. These steps may be carried out once or twice or more. From the viewpoint of obtaining a thick film having excellent smoothness, the steps of applying the modified dispersion, drying and baking may be carried out multiple times. For example, the modified dispersion liquid is applied to a substrate, and the liquid dispersion medium is removed by heating to form a film. The modified dispersion liquid may be further applied onto the formed film, the liquid dispersion medium is removed by heating, and the F polymer is further baked by heating to form an F layer. Alternatively, the modified dispersion liquid may be applied to a substrate, the liquid dispersion medium may be removed by heating to form a film, and the F polymer may be further baked by heating to form a baked film. The modified dispersion liquid may be further applied on the baked film, the liquid dispersion medium may be removed by heating, and the F polymer may be further baked by heating to form a baked film, thereby forming an F layer.
[0058] In the latter case, it is considered that the gaseous decomposition product of the non-fluorinated leveling agent or the atmospheric gas when the modified dispersion liquid is applied is present at the boundary between the fired films in the F layer, and that this makes it easy for a minute space to be formed. The presence of this minute space is considered to alleviate the difference in stress between the fired films caused by the expansion and contraction of the F polymer, and the laminate has excellent low linear expansion properties. The thickness of the F layer is preferably 25 μm or more, more preferably 50 μm or more. The upper limit of the thickness is 200 μm. The modified dispersion has excellent film-forming properties, so that such a thick film can be formed well, and within this range, an F layer with excellent crack resistance can be easily formed. The peel strength between the F layer and the base layer is preferably 10 N / cm or more, more preferably 15 N / cm or more. The peel strength is preferably 100 N / cm or less. By using the modified dispersion, such a laminate can be easily formed without impairing the physical properties of the F polymer in the F layer.
[0059] The porosity of the F layer is preferably 5% or less, more preferably 4% or less, and is preferably 0.01% or more, more preferably 0.1% or more. The porosity is determined by determining the void area of the F layer through image processing of a SEM photograph of the cross section of the molded product observed with a scanning electron microscope (SEM), and dividing the area occupied by the void area by the area of the F layer (%). The area occupied by the void area is calculated by approximating the void area as a circle.
[0060] Examples of the substrate include metal substrates such as metal foils made of copper, nickel, aluminum, titanium, and alloys thereof; heat-resistant films made of heat-resistant resins such as polyimide, polyarylate, polysulfone, polyarylsulfone, polyamide, polyetheramide, polyphenylene sulfide, polyaryletherketone, polyamideimide, liquid crystalline polyester, liquid crystalline polyesteramide, and tetrafluoroethylene-based polymer; prepregs which are precursors of fiber-reinforced resin substrates; and glass substrates. The shape of the substrate may be flat, curved or uneven, and may further be any of foil, plate, film and fiber.
[0061] When the substrate is a metal foil, the substrate may be a low-roughening metal foil or a non-roughening metal foil. The substrate is preferably a non-roughening metal foil, more preferably a non-roughening copper foil. In this case, the F layer has excellent adhesion to the substrate, so that the laminate tends to have excellent peel strength. In this case, the printed circuit board formed from the laminate tends to have excellent transmission characteristics.
[0062] The ten-point average roughness of the surface of the substrate is preferably 0.1 μm or less, more preferably 0.05 μm or less. The ten-point average roughness is preferably 0.001 μm or more. Even with such an unroughened substrate, the laminate can form a printed circuit board or the like having excellent peel strength and transmission characteristics. The ten-point average roughness of the surface of the substrate is a value specified in Appendix JA of JIS B 0601:2013. The thickness of the substrate is preferably 2 to 100 μm. When the substrate is a metal foil, the thickness of the substrate is preferably 1 to 35 μm. The substrate may also be a metal foil with a carrier, which is an ultra-thin copper foil (thickness 2 to 5 μm) laminated on a carrier copper foil via a release layer.
[0063] Specific examples of the laminate include a metal-clad laminate having a metal foil and an F layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and an F layer on both surfaces of the polyimide film. These laminates are excellent in various physical properties such as electrical properties, and are suitable as printed circuit board materials, etc. Specifically, such laminates can be used for manufacturing flexible printed circuit boards and rigid printed circuit boards.
[0064] One embodiment of the laminate is a laminate of prepreg / F layer / metal foil. The substrate is preferably a prepreg having a polymer layer on the surface of a glass cloth obtained by impregnating a heat-resistant resin that may be contained in the substrate. The polymer layer may be formed of a plurality of polymer layers, and in such a case, each polymer layer is preferably formed of a different polymer. If an F layer is present between the prepreg and the metal foil, the prepreg and the metal foil are less likely to peel off, which is preferable. This laminate is useful as antenna parts, printed circuit boards, aircraft parts, automobile parts, sporting goods, food industry products, heat dissipation parts, paints, cosmetics, etc. In the case of printed circuit boards, it can also be used as a new printed circuit board material to replace conventional glass epoxy boards in order to prevent temperature rise in printed circuit boards on which electronic components are densely mounted.
[0065] Specifically, the laminate can be used in a wide variety of applications, including wire coating materials for aircraft wires and the like, enameled wire coating materials used in motors for electric vehicles and the like, electrical insulating tape, insulating tape for oil drilling, materials for printed circuit boards, separation membranes such as microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, and gas separation membranes, electrode binders for lithium secondary batteries, fuel cells, and the like, copy rolls, covers for furniture, automobile dashboards, home appliances, and the like, sliding members such as load bearings, sliding shafts, valves, bearings, bushes, seals, thrust washers, wear rings, pistons, slide switches, gears, cams, belt conveyors, and food transport belts, wear pads, wear strips, tube lamps, test sockets, wafer guides, wear parts for centrifugal pumps, hydrocarbon, chemical, and water supply pumps, tools such as shovels, files, cutters, and saws, boilers, hoppers, pipes, ovens, baking molds, chutes, dies, toilets, container coating materials, power devices, transistors, thyristors, rectifiers, transformers, and power MOS Useful for FET, CPU, heat sink, metal heat sink. More specifically, the present laminate is useful as a sealing material for processing machines, vacuum ovens, plasma processing devices, and the like that perform heat treatment under low oxygen conditions, for example, in housings for personal computers and displays, materials for electronic devices, and the interior and exterior of automobiles, and as a heat dissipation component in processing units for sputtering and various dry etching devices.
[0066] The dispersion of the present invention (hereinafter also referred to as "the present dispersion") contains F particles, inorganic particles, a liquid dispersion medium, and at least one non-fluorine-based leveling agent selected from the group consisting of (meth)acrylic leveling agents, silicone leveling agents, and alcohol alkoxylates, and the proportion of the F particles and the proportion of the inorganic particles in the total amount are 5 to 40 mass% and 20 to 60 mass%, respectively. The definitions and ranges of the F particles, inorganic particles, liquid dispersion medium, and non-fluorinated leveling agent in the present dispersion, including preferred embodiments thereof, are the same as those in the present method. The present dispersion may further contain an aromatic polymer, a nonionic surfactant, a pH adjuster, a pH buffer, an additive, etc. The definitions and ranges of the aromatic polymer, the nonionic surfactant, the pH adjuster, the pH buffer, and the additive in the present dispersion, including preferred embodiments thereof, are the same as those in the present method.
[0067] The present dispersion may be produced by this method or another method, but is preferably produced by this method, in which case aggregation of the F particles is easily eliminated and the present dispersion is likely to have excellent dispersion stability. Other methods include a method in which F particles, inorganic particles, a liquid dispersion medium, and a non-fluorine-based leveling agent are added all at once and mixed; a method in which a non-fluorine-based leveling agent is added to a liquid dispersion medium, and then F particles and inorganic particles are added in sequence and mixed; and a method in which F particles and inorganic particles are premixed with a liquid dispersion medium and a non-fluorine-based leveling agent, respectively, and the two resulting mixtures are further mixed. The mixing method and mixing device may be the same as those used in the present method. EXAMPLES
[0068] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Preparation of each component and material [F particle] F particle 1: containing 97.9 mol% TFE units, 0.1 mol% NAH units and 2.0 mol% PPVE units, in that order, and having a carbonyl group-containing group with a main chain carbon number of 1×10 6 Particles made of F polymer 1 with 1000 particles per particle and a melting temperature of 300°C (D50: 2.1 μm) F Particle 2: Particles made of non-thermofusible PTFE (D50: 0.3 μm) [F dispersion] F dispersion 1: Aqueous dispersion containing 60% by mass of F particles 2 (AGC Corporation, product number AD-915E)
[0069] [Inorganic particles] Inorganic particle 1: Spherical silica with a D50 of 1 μm that has been surface-treated with phenylaminosilane [non-fluorinated leveling agent] Leveling agent 1: Polyether modified acrylate (BYK Japan, "BYK-381") [Aromatic resin varnish] Varnish 1: Water varnish containing a precursor of aromatic polyamideimide (PAI1, acid value: 50 mg KOH / g) (Showa Denko Materials, "HPC-1000") [Nonionic surfactants] Surfactant 1: Nonionic surfactant (BYK Japan, "BYK-3450")
[0070] 2. Example of modified dispersion liquid production (Example 1) First, F particles 1, inorganic particles 1, varnish 1, surfactant 1, ammonia water, and ammonium hydrogen carbonate were added to a pot, and zirconia balls were then added. The pot was then rolled at 150 rpm for 1 hour to prepare raw dispersion 1 (content of inorganic particles 1: 45% by mass). In a separate pot, the raw dispersion liquid 1 and the leveling agent 1 were added, and zirconia balls were added. After that, the pot was rolled at 150 rpm for 1 hour, and then F dispersion liquid 1 was added to the pot, and the pot was rolled at 150 rpm for 1 hour, to obtain a modified dispersion liquid 1 (viscosity: 300 mPa s, pH: 8.0) containing F particles 1 (18.5 parts by mass), F particles 2 (20 parts by mass), inorganic particles 1 (60 parts by mass), PAI 1 (1.5 parts by mass), surfactant (1 part by mass), leveling agent 1 (2 parts by mass), ammonia water (100 parts by mass), and ammonium bicarbonate as a whole. The surface tension of the modified dispersion 1 was lower than that of the original dispersion 1, the difference being 0.1 to 1 mN / m, and the dispersion layer rate was 60% or more.
[0071] 3. Example of laminate manufacturing The modified dispersion 1 was applied to the surface of a long non-roughened copper foil (surface ten-point average roughness: 0.1 μm or less, thickness: 18 μm) using a bar coater to form a wet film. The copper foil on which the wet film was formed was then passed through a drying oven at 110° C. for 5 minutes and dried by heating to obtain a dry film. The dry film was then heated at 380° C. for 3 minutes in an oven in a nitrogen gas atmosphere. This produced a laminate 1 having a copper foil and a polymer layer (thickness: 50 μm) as a molded product on its surface, which contained F polymer 1, PTFE, inorganic oxide particles 1, and PAI 1. When a laminate was produced in the same manner as in Laminate 1 except that Original Dispersion 1 was used instead of the Modified Dispersion, cracks were generated in the polymer layer having a thickness of 100 μm.
[0072] The copper foil of the laminate 1 was removed by etching with a ferric chloride aqueous solution to prepare a single polymer layer, and the dielectric loss tangent was measured by the SPDR (split post dielectric resonance, measurement frequency: 10 GHz) method. As a result, the dielectric loss tangent of the polymer layer was 0.0010 or less. The copper foil of the laminate 1 was removed by etching with an aqueous solution of ferric chloride to prepare a single polymer layer, and a square test piece measuring 180 mm on each side was cut out. The linear expansion coefficient of the cut test piece was measured in the range of 25 to 260°C according to the measurement method specified in JIS C 6471:1995. The linear expansion coefficient of the test piece was 30 ppm / °C or less.
[0073] A rectangular test piece with a length of 100 mm and a width of 10 mm was cut out from the laminate 1. The test piece was fixed at a position 50 mm from one end in the longitudinal direction, and the copper foil and the polymer layer were peeled off from one end in the longitudinal direction at an angle of 90° to the test piece at a pulling speed of 50 mm / min. The maximum load at the time of peeling was taken as the peel strength (N / cm). The peel strength of the laminate 1 was 10 N / cm or more. Furthermore, the inorganic particles 1 were firmly supported in the polymer layer and did not fall off. [Industrial Applicability]
[0074] As is clear from the above results, the modified dispersion liquid prepared by this method has excellent dispersion stability and film-forming properties, and the F layer obtained by applying it to the substrate has excellent electrical properties and low linear expansion. In addition, the F layer and the substrate layer have excellent adhesion, and the inorganic particles are firmly supported in the F layer. Therefore, it is considered that the laminate formed from the modified dispersion liquid obtained by this method has excellent uniformity of component distribution and highly expresses the properties of the F polymer and inorganic particles. In addition, it is considered that no voids are generated at the interface of the layers, and the decrease in water resistance is suppressed.
Claims
1. A method for producing a modified dispersion liquid, comprising adding at least one non-fluorine-based leveling agent selected from the group consisting of (meth)acrylic leveling agents, silicone leveling agents and alcohol alkoxylates to a dispersion liquid containing particles of a tetrafluoroethylene-based polymer having a melting temperature of 200 to 325°C, inorganic particles, and a liquid dispersion medium, wherein the proportion of the inorganic particles in the total amount is 20 to 60 mass %, thereby reducing the surface tension of the dispersion liquid to obtain a modified dispersion liquid.
2. The method according to claim 1 , wherein the particles of the tetrafluoroethylene-based polymer include particles of a heat-fusible tetrafluoroethylene-based polymer and particles of a non-heat-fusible tetrafluoroethylene-based polymer.
3. The method according to claim 1 or 2, wherein the tetrafluoroethylene polymer is a tetrafluoroethylene polymer having a carbonyl group-containing group or a hydroxyl group-containing group.
4. The method according to any one of claims 1 to 3, wherein the inorganic particles are silica particles.
5. The method according to any one of claims 1 to 4, wherein the liquid dispersion medium is at least one selected from the group consisting of water, amides, ketones, and esters.
6. The method according to any one of claims 1 to 5, wherein the difference between the surface tension of the modified dispersion and the surface tension of the dispersion is 1 mN / m or less.
7. The method according to any one of claims 1 to 6, wherein the dispersion further comprises an aromatic polymer.
8. The method according to any one of claims 1 to 7, wherein the dispersion further contains a nonionic surfactant.
9. A method for producing a laminate, comprising: applying the modified dispersion obtained by the production method according to any one of claims 1 to 8 to a surface of a substrate; heating the surface of the substrate; and forming a polymer layer containing the tetrafluoroethylene-based polymer and the inorganic particles. A method for producing a laminate, comprising: obtaining a laminate having a substrate layer constituted by the substrate and the polymer layer.
10. The method of claim 9, wherein the polymer layer has a thickness of 25 μm or more.
11. The method according to claim 9 or 10, wherein the ten-point average roughness of the surface of the substrate is 0.1 μm or less.
Citation Information
Patent Citations
Fluoropolymer composition and its production
JP1994088000A
Coating compositions, articles, and methods of coating articles
JP2009532517A
Non-aqueous dispersion of polytetrafluoroethylene
JP2016194017A
Nonaqueous dispersion of fluororesin, fluororesin-containing thermosetting resin composition prepared therewith and cured product thereof
JP2017210549A
Fluorine-based resin non-aqueous dispersion, fluorine-based resin-containing thermosetting resin composition based on the same, and cured product thereof
JP2020186351A